Acquired Vulvar Lymphangioma Following CO2 Laser Treatment for Sebaceous Gland Nevus in a 10-Year-Old Girl: A Case Report - Luo Y; Chen W; Xu D; Chen S; Ma S (Clinical, Cosmetic and Investigational Dermatology)
Yuwu Luo,* Weifeng Chen,* Duanni Xu, Shuting Chen, Shaoyin Ma Guangzhou Dermatology Hospital, Guangzhou, Guangdong, 510095, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shaoyin Ma, Guangzhou Dermatology Hospital, 56 hengfu Road, Guangzhou, 510095, People’s Republic of China, Email msymsb315@163.comAbstract: Acquired vulvar lymphangioma (AVL) is a rare condition characterized by abnormal lymphatic vessels in the vulva. We describe a 10-year-old female patient who presented with vulvar swelling for 23 days. She has no history of sexual assault and irradiation. Two months ago, the patient underwent CO2 laser surgery for a sebaceous gland nevus on the left labia majora, resulting in delayed healing and residual scar tissue. Twenty-three days ago, swelling appeared in the external genitalia, accompanied by mild pain that worsened after activity and lessened when lying down. Treatment with anti-infection and anti-allergy medications at the previous hospital did not show significant improvement. Histopathological examination and genetic testing confirmed Our diagnosis of acquired vulvar lymphangioma with lymphedema.Keywords: acquired vulvar lymphangiectasia, lymphangioma, lymphedema